2007
DOI: 10.3346/jkms.2007.22.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Profiles of CpG Island Loci in Major Types of Human Cancers

Abstract: Several reports have described aberrant methylation in various types of human cancers. However, the interpretation of methylation frequency in various human cancers has some limitations because of the different materials and methods used for methylation analysis. To gain an insight into the role of DNA hypermethylation in human cancers and allow direct comparison of tissue specific methylation, we generated methylation profiles in 328 human cancers, including 24 breast, 48 colon, 61 stomach, 48 liver, 37 laryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…11 However, the role of RUNX3 as a possible gastric tumor suppressor is yet controversial. 7,12,[14][15][16] Moreover, the results of present study are not consistent with those of the previous reports in that the positive MSP expression of the RUNX3 gene was found only in 32.9% of the patients, which is relatively lower than those of the previous reports (45-69%), 7,8 including the Korean-specific data (56-64%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 However, the role of RUNX3 as a possible gastric tumor suppressor is yet controversial. 7,12,[14][15][16] Moreover, the results of present study are not consistent with those of the previous reports in that the positive MSP expression of the RUNX3 gene was found only in 32.9% of the patients, which is relatively lower than those of the previous reports (45-69%), 7,8 including the Korean-specific data (56-64%).…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, methylation of the multiple tumor suppressor genes including RUNX3 were found to increase with age in the nonneoplastic gastric epithelia. 13 Although the absence of RUNX3 expression has been reported in several studies on the human gastric carcinoma, 7,11,12,14,15 a recent study reported that the immunohistochemical staining detected the RUNX3 protein expression in the infiltrating leukocytes, but not in the gastric epithelium. 16 Therefore, the low levels of RUNX3 expression in the gastric epithelium and the absence of downregulation of RUNX3 in the gastric cancer do not support the idea that RUNX3 functions as a gastric tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is the most common and important mechanism of TSGs inactivation in various human carcinoma (Grønbaek et al, 2007;Dachrut et al, 2009). It's worth noting that hypermethylation of TSGs may occur in early stage of carcinogeneses of dysplasia cells (Park et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] CpG methylation has recently been shown to be an important mechanism in the transcriptional inactivation of E-cadherin, and CpG methylation around the promoter region of E-cadherin was found to be significantly correlated with reduced E-cadherin expression in various cancers. 14 Though it has been thought that hypermethylation of the E-cadherin gene is associated with immunohistochemical expression, tumor progression, tumor grade, tumor invasion, and lymph node metastasis in various tumors, this has been rarely studied in endometrial carcinoma of Korean women. In the current study, we analyzed methylation status of the E-cadherin and E-cadherin expression in endometrial hyperplasias and endometrial carcinomas.…”
Section: Introductionmentioning
confidence: 99%